Smoky, the Dog That Saved My Life : The Bill Wynne Story - Pimm, Nancy Roe (Book collections on Project MUSE., 2019)
"World War II soldier Bill Wynne met Smoky while serving in New Guinea, where the dog, who was smaller than Wynne's army boot, was found trying to scratch her way out of a foxhole. After he adopted her, she served as the squadron mascot and is credited as being the first therapy dog for the emotional support she provided the soldiers. When they weren't fighting, Bill taught Smoky hundreds of tricks to entertain the troops. Smoky became a war hero herself at an airstrip in Luzon, the Philippines, where she helped save forty airplanes and hundreds of soldiers from imminent attack. After the war, Bill worked as a Hollywood animal trainer and then returned to his hometown of Cleveland, Ohio. He and Smoky continued to perform their act, even getting their own TV show, How to Train Your Dog with Bill Wynne and Smoky."--Provided by publisher